Dopamine receptor type 1 of Caenorhabditis elegans expressing in mechanosensory neurons - Stadnyk, V.V.; Regosh A.; Mayor, C.Y.; Fomenko, I.S.; Bondarchuk, T.I.; Sklyarov, O.Y. (Вiopolymers and Cell, 2012)
Until now the results on profiling dopamine receptors in C. elegans have been incomplete and fragmentary. The aim of this study was to investigate the expression profile of dop-1 gene in C. elegans using 3 kb promoter with 3'-end locating before ATG of dop-1 gene. Methods. The strain of C. elegans with mutant unc-119 gene was used. To check a pattern of the dop-1 expression, the promoter of this gene was amplified using PCR. The animals were co-bombarded with plasmid pPD95.77 dop-1::GFP and reporter construct containing unc-119 gene. Results. Using GFP as a reporter protein, we built a whole picture of expression of dopamine receptor type 1 in C. elegans and found that this protein could be detected only in mechanosensory neurons such as PLM, PVQR, PVQL, ALNR, ALNL, DVAR, DVC. Keywords: dopamine receptors, mechanosensory neurons, Caenorhabditis elegans, expression